Pemanfaatan Potensi Produk Fermentasi “Tempe” Sebagai Pangan Fungsional: Systematic Literature Review - Devy Yuliantari; Anita Rahmiwati; Nur Alam Fajar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
As a cheap and healthy vegetable protein, tempeh is widely consumed. The fermentation method can increase and maintain the nutritional value of tempeh made from raw materials using the Rhizopus oligosporus fungus, while softening the texture to make it easier to consume. Tempeh is becoming increasingly popular among Indonesians due to its low price, delicious taste, high nutritional value, potential health benefits, and versatility in culinary preparation. Various studies on tempeh have been carried out by researchers from various countries, especially Japan, Germany, England and the United States. Soybean tempeh is more popular and liked by many people because of its soft texture and white color. This article uses the Systematic Literature Review (SLR) technique, a methodical process for identifying, assessing, and interpreting all research materials related to the research subject. From the table above it is clear that of the 4,357 articles taken, only 8 articles were used as references to write this article; only 8 articles were able to provide answers to the research questions. One of the functional foods is tempeh, which is food made from soybeans (Glicyne max) which has been fermented with the help of the microbe Rhizopus sp. As a fermented product, tempeh has additional macro and micro nutrients that the body needs. Therefore, foods like this are very good for those who are malnourished and can help meet the body's nutritional needs.